(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تم تحديد تركيز كل من Pb, Cu, Cd, Co, Cr , Mn Zn, Fe, في الترسبات الغبارية التي جمعت لمدة ثلاثين يوماً وأخرى لمدة ستين يوماً من كل فصل وموزعة على عشر مناطق تم اختيارها بعناية على شاطئ مدينة اللاذقية, بحيث تكون متاخمة للمياه البحرية الساحلية وغير متأثرة نسبياً بالأنشطة البشرية والصناعية. بعد جمع العينات تم تهضيمها بواسطة حمض الآزوت ومن ثم الكشف عن العناصر باستخدام تقنية الامتصاص الذري. أظهرت النتائج أن تراكيز كل من Cu, Mn, Zn , Fe تزداد في هواء شاطئ مدينة اللاذقية و تنخفض تدريجياً كلما اتجهنا نحو الداخل, وتعتبر الأمواج البحرية مسؤولة عن شحن هواء الشاطئ بمركبات تلك العناصر. In this study, the concentration of Zn, Cu, Fe, Mn, Pb, Cd, Co, Cr were determined in a dust trap samples, collected for four seasons every 30 days and 60 days from eight sites distributed at Latakia city. All the sites were near the coast. The samples were digested by nitric acid and the elements were determined by the atomic absorption spectroscopy. The results showed that the concentrations of metals Zn, Cu, Fe, Mn, increased in the coastal air of Latakia city and gradually decreased into to the sectors far from the coast, so it presumed that the sea waves are responsible of charging the coastal air with metallic compounds.